2020
DOI: 10.1111/hel.12704
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences betweenHelicobacter pyloriinfection and cholesterol levels in an adult health checkup program

Abstract: BackgroundHelicobacter pylori (H pylori) infection is suggested to be a risk factor of metabolic syndrome (MS) and lipid abnormalities. The aim of this study was to investigate the influence of H pylori infection on MS and lipid abnormalities according to sex differences.Materials and MethodsWe analyzed a total of 4551 adults who received health checkups from January 2016 to May 2017. We enrolled participants who did not have a history of hypertension, diabetes, hyperlipidemia, or cancer among those who underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…In the current study, H. pylori-infected patients had higher mean lipid profiles for TC, TG, and LDL-c. Similarly, previous studies indicated that H. pylori seropositive subjects had higher serum triglyceride, total cholesterol, and LDL-c concentrations when compared to healthy subjects [59,60,61,62,63,64]. Our findings were also in agreement with another Korean study which showed that H. pylorus was independently associated with an increased level of TC, and LDL-C [65].…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, H. pylori-infected patients had higher mean lipid profiles for TC, TG, and LDL-c. Similarly, previous studies indicated that H. pylori seropositive subjects had higher serum triglyceride, total cholesterol, and LDL-c concentrations when compared to healthy subjects [59,60,61,62,63,64]. Our findings were also in agreement with another Korean study which showed that H. pylorus was independently associated with an increased level of TC, and LDL-C [65].…”
Section: Discussionsupporting
confidence: 92%
“…This observation is in line with previous bariatric studies reporting a predominance of women undergoing bariatric surgery [ 75 , 76 ]. Additionally, Hp -I is known in the literature to affect more women than men [ 77 , 78 ], although studies reporting a male predominance ought to be equally acknowledged [ 79 ]. Furthermore, estradiol-treated gerbils exhibited more intense and extended acute and follicular gastritis, compared to the control group [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some possible insights include the following: females appear to exhibit a higher Hp burden than males [ 83 ]. Likewise, Hp (+) females display significantly decreased HDL cholesterol concentrations than males, whereas total cholesterol, LDL cholesterol, and triglycerides are statistically higher in Hp (+) males, thereby signifying that Hp might affect lipid profiles and may be different by gender [ 78 ]. Moreover, the mentioned T2DM, a component of MetS, and Hp -I have synergistic effects on gastric oncogenesis [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…8 Although the effect of H. pylori eradication on MS and dyslipidemia has not been investigated, a retrospective study from Korea reported that H. pylori infection is associated with increased total cholesterol in males and decreased HDL cholesterol in females. 9 A recent Korean retrospective cohort study demonstrated that successful H. pylori eradication reduced the risk of developing low HDL cholesterol in females and high LDL cholesterol in males. 10 The baseline BMI differed between H. pylori-persistent and H. pylori-eradicated groups, but sex-specific subgroup analysis for BMI was not performed.…”
mentioning
confidence: 99%